A Quasi Experimental Study on Hand Hygiene Practices among Secondary School Children in Khyber PakhtunKhwa - Rehana Malik, Farhat; Asif Reman; Aimen Niazi; Faryal Kifayat; Nayab Afridi; Sonila Khan; Kainat Khan (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the effectiveness of hand-hygiene training on handwashing practices among schoolchildren. Method: The quasi-experimental study was conducted from 1st August- 2018 to 5th October- 2018 in four secondary schools in Peshawar and Kohat districts of Khyber Pakhtunkhwa, Pakistan, and comprised male students grades 5, 6, 7, 9 and 10. They were given a live demonstration about the standard steps of hand-hygiene as per the World Health Organisation checklist, and they were shown the steps in pictorial form as well to reinforce the message. Pre- and post-intervention scores were recorded on the 14- point checklist. Data analysed using SPSS 23. Results: There were 200 boys with a mean age of 13.23±0.92 years (range: 11-16 years); 87(43.5%) of them being from grade 7. Post-intervention score increased significantly compared to the baseline (p<0.01). Significant differences were identified with respect to geographical location, type of school, grade in school and mothers’ education (p<0.05). Conclusion: Hand-hygiene training significantly increased students’ hand-washing practices and behaviours. Key Words: Hand washing, Hand h, Secondary school, Training, Practices.